HISTORICAL NOTE ON THE EVOLUTION OF THE PARTICIPLE - Hamzayev Hasan (Journals Park Publishing, 2023)
The French participles go back to the corresponding participles of Latin, except the compound form and passive form of the present participle. The past participle comes from the participium perfecti passivi, the present participle from the participium praesentis activi. Both Latin forms agreed with the noun, the first in gender and number: dictus-dicti, dicta-dictae, etc., the second in number: cantans-cantantes. Both forms were available. Nowadays, the present participle is invariable. The gerund goes back to the Latin gerundium, but in French it represents a completely new grammatical category. In Latin, it was a noun.
Keywords: participle, past participle, French language, gerund, present participle, gerundium, passing.